Klimaschutz im Luftverkehrsrecht Eine Analyse klimaschützender Regelungen und ihrer Wechselwirkungen aus clubtheoretisch informierter, rechtswissenschaftlicher Perspektive am Beispiel des Luftverkehrssektors - Dilg, Theresa (Studien zu Staat, Recht und Verwaltung, 2022)
The climate relevance of air traffic should not be underestimated. The already advanced legal containment of CO2 emissions caused by aviation is the focus of this study. The central actors - the International Civil Aviation Organization (ICAO) as an international organization and the EU as a supranational organization, as well as the UNFCCC regime as a framework - create a plural regulatory environment. The work discloses this regulatory environment and examines its interactions as well as possibilities for development. Special attention is paid to the Carbon Offsetting and Reduction Scheme (CORSIA) of the ICAO and the European Emissions Trading Scheme (EU ETS).